Levels of Paraoxonase-1 Activity, Immunological Parameters, and Antioxidant Enzymes in Children Infected with Entamoeba Histolytica - Shakor, Donia Suad (Journal of Discoveries in Applied and Natural Science, 2026)
Introduction & Objective: Entamoeba histolytica (E. histolytica) is an important enteric protozoan leading to morbidity in children, and is frequently accompanied with oxidative stress and immune stimulation. The purpose of this study was to evaluate the activity of Paraoxonase-1 (PON1) status, antioxidant enzymes (GSH, TAC, Catalase) and immunological parameters (IL‑6, IL‑10) in E. histolytica‑infected children. Materials & Methods: One hundred fifty children were enrolled during the period from May to September, 2025 at the Pediatric Hospital-Kirkuk-Iraq, including ninety children with diarrhea and sixty healthy controls. Stool microscopy confirmed infection. The levels of PON1, antioxidant enzymes, and cytokines in the serum were assayed using commercially available kits (Sunlong Biotechnology, China). Results: Among diarrheal children, 33 (36.7%) were positive for E. histolytica. Compared with controls, infected children had lower GSH (4.12 ± 1.23 vs 6.81 ± 1.05 µmol/L), TAC (0.83 ± 0.19 vs 1.31 ± 0.21 mmol Trolox Eq/L), and PON1 activity (45.23 ± 9.87 vs 89.56 ± 14.32 U/L), and higher catalase (224.55 ± 49.78 vs 179.65 ± 34.92 kU/L), IL‑6 (16.24 ± 6.71 vs 4.53 ± 1.21 pg/mL), and IL‑10 (13.11 ± 5.22 vs 6.98 ± 2.03 pg/mL) (all P < 0.05). Pearson correlation showed positive associations among antioxidant markers (GSH–TAC r = 0.72, GSH–PON1 r = 0.65) and negative correlations with cytokines (GSH–IL‑6 r = –0.61, GSH–IL‑10 r = –0.42). Conclusions: E. histolytica infection in children decreases antioxidant defense and increases inflammatory cytokines suggesting a synergistic effect of oxidative stress and immune response.